FGF-2 deficiency causes dysregulation of Arhgef6 and downstream targets in the cerebral cortex accompanied by altered neurite outgrowth and dendritic spine morphology - Baum, Philip; Vogt, Miriam A.; Gass, Peter; Unsicker, Klaus; Bohlen und Halbach, Oliver von (International journal of developmental neuroscience, 2016)
Fibroblast growth factor 2 (FGF-2) is an abundant growth factor in the brain and exerts multiple functions on neural cells ranging from cell division, cell fate determination to differentiation. However, many details of the molecular mechanisms underlying the diverse functions of FGF-2 are poorly understood. In a comparative microarray analysis of motor sensory cortex (MSC) tissue of adult knockout (FGF-2-/-) and control (FGF-2+/+) mice, we found a substantial number of regulated genes, which are implicated in cytoskeletal machinery dynamics. Specifically, we found a prominent downregulation of Arhgef6. Arhgef6 mRNA was significantly reduced in the FGF-2-/- cortex, and Arhgef6 protein virtually absent, while RhoA protein levels were massively increased and Cdc42 protein levels were reduced. Since Arhgef6 is localized to dendritic spines, we next analyzed dendritic spines of adult FGF2-/- and control mouse cortices. Spine densities were significantly increased, whereas mean length of spines on dendrites of layer V of MSC neurons in adult FGF-2-/- mice was significantly decreased as compared to respective controls. Furthermore, neurite length in dissociated cortical cultures from E18 FGF-2-/- mice was significantly reduced at DIV7 as compared to wildtype neurons. Despite the fact that altered neuronal morphology and alterations in dendritic spines were observed, FGF-2-/- mice behave relatively unsuspicious in several behavioral tasks. However, FGF-2-/- mice exhibited decreased thermal pain sensitivity in the hotplate-test.
Gesehen am 29.04.2019